Perancangan Model Ontologi untuk Representasi Pengetahuan Cagar Budaya Masa Kolonial di Indonesia - I Gede Widiantara Mega Saputra,; Gst. Ayu Vida Mastrika Giri, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
This study aims to develop an ontology model that represents knowledge about cultural heritage from the colonial era in Indonesia, an important effort in preserving and educating about cultural heritage. In the process, this ontology model is constructed using Protégé, a free and open-source ontology development platform that supports various formats including OWL (Web Ontology Language). By utilizing the Methontology methodology, this model ensures systematic and structured development. The structure of the ontology model includes one main class with four subclasses, which assists in the logical categorization of information and supports in-depth analysis. Testing the model using SPARQL queries confirms the accuracy and correctness of the data structure. The findings of this study indicate that the developed ontology successfully achieves its set objectives, not only in documenting information effectively but also in enriching methods of presenting and analyzing knowledge about cultural heritage. This opens the way for further research and practical applications in the preservation and education of cultural heritage, underlining the importance of digitalization in historical preservation.
Keywords: Cultural Property, Ontology, Methontology, Protégé